2016
DOI: 10.1063/1.4961104
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic analysis of the Milad Tower

Abstract: Abstract. This report involves the modelling of the Milad Tower using the finite element analysis program Strand7. A dynamic analysis was performed on the structure in order to understand the deflections and stresses as a result of earthquake and wind loading. In particular, Linear Static as well as Natural Frequency and Spectral Response solvers were used to determine the behaviour of the structure under loading. The findings of the report highlight that the structure was modelled accurately with the outputs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 4 publications
(1 reference statement)
0
6
0
Order By: Relevance
“…Figure 2 shows the position of acceleration sensors. A number of numerical and experimental studies have been carried out to identify dynamic characteristics of the building and enhance the performance of the tower against lateral loads 33–36 . In most cases, FFT is used to recognize the tower's condition.…”
Section: Numerical Investigation Of the Proposed Methods In Case Stud...mentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 2 shows the position of acceleration sensors. A number of numerical and experimental studies have been carried out to identify dynamic characteristics of the building and enhance the performance of the tower against lateral loads 33–36 . In most cases, FFT is used to recognize the tower's condition.…”
Section: Numerical Investigation Of the Proposed Methods In Case Stud...mentioning
confidence: 99%
“…A number of numerical and experimental studies have been carried out to identify dynamic characteristics of the building and enhance the performance of the tower against lateral loads. [33][34][35][36] In most cases, FFT is used to recognize the tower's condition. 4) and ( 5), the best segment for each channel is selected.…”
Section: Introduction Of Milad Towermentioning
confidence: 99%
“…Therefore, developing a high-fidelity FEM of the complex structures takes considerable effort [19]. To perform a dynamic analysis [20] of Milad Tower (shown in Fig. 1), a reliable FEM is carried out by Strand7 software [21], which can be implemented in future damage detection methodologies.…”
Section: Introductionmentioning
confidence: 99%
“…There was Hurricane Mujigae, two hurricane-related hurricanes in October 2015 in Guangdong, China, and a tornado in June 2016 in Yancheng, China. Considering the effects of lateral wind and earthquake loads on Milad Tower, Wilhelm et al [5] evaluated the dynamic behavior of Milad Tower. A thorough study has been conducted to study the effects of wind on this tower by Yahyai et al [6].…”
mentioning
confidence: 99%
“…As a result of Cheng and Fu's [13] study, hemispherical domes have been investigated for turbulent and laminar boundary layer flow. A study by the authors found that the sensitivity of pressure distribution on the hemisphere decreased as the Reynolds number increased above (1-2) ×10 5 for the turbulent boundary layer flow. Using machine learning techniques, Hu and Kwok [14] collected wind data for different cylindrical engineering structures at various Reynolds numbers and provided statistical aerodynamic estimations.…”
mentioning
confidence: 99%